PEMBINAAN KEPEMIMPINAN ORANG MUDA KATOLIK: DI PAROKI KUALA DUA DAN BEDUAI KEUSKUPAN SANGGAU - Kristianus, Kristianus; Prasetyo, Laurentius; Kuslin, Thomas; Magdalena, Magdalena; Lala, Carolina; Lodo, Mikael Dou (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
This activity is motivated by developments in science and technology, especially in the field of telecommunications, which are currently sweeping the world. As future leaders of the people who are expected by the church to be able to actively develop church life, they are required to be wiser and able to teach young Catholics around them regarding the main negative impacts of the development of telecommunications technology. With the development of science and digital, humans experience amnesia, forgetting their identity. This is also what is happening to young Catholics in the Sanggau Diocese who are being hit by the mastery of science and the development of the digital world. This community service was carried out for two days, in the Beduai parish in the Sanggau Diocese. The method of this activity is education for young people, starting with the presentation of material in each session and continuing with reflection in the form of revealing responses from the participants. The atmosphere of the activity was held in a lively manner accompanied by music. This activity was successful in increasing teenagers' understanding of leadership and efforts to overcome the impact of developments in communication technology that could threaten their Catholic faith.